Increa sing The Ability Of Health Care Administrators In Handling The Fever Of The Fever Through Training For Early Crime Handling - Suparjo Suparjo; Fatchurrozak H; Nurcholis Nurcholis; Cuciati Cuciati (Jurnal Berkarya Pengabdian Masyarakat, 2019)
Febrile seizures are a common case in children. Seizures are frightening events for parents, especially if the seizure is the first time experienced by a child. Prompt and proper handling is needed to avoid the worse consequences caused by seizure. This community service aims to ensure that the health cadres in particular can understand and have the ability to manage early febrile seizures in children. The method used is active and participatory learning through several stages, namely socialization; implementation consisting of observing the level of knowledge through pretest, providing training through classical materials and practices related to febrile seizures in children and early treatment of febrile seizures as well as prevention methods, and posttest; assistance and evaluation. The results of the pretest and posttest evaluations after training in the form of materials and practices for health cadres in the Bandung village there was an increase in knowledge and skills. Before the training and mentoring, most of them had less knowledge, that is 50% and only a small portion had good knowledge, which was 15%. After getting training and assistance most of them have good knowledge which is 50% and only a small portion is lacking which is 10%. Keywords : Training, Early Treatment for Fever Seizures